An experimental study on pseudoelasticity of a NiTi-based damper for civil applications. (18th September 2017) - Nespoli, Adelaide; Bassani, Enrico; Torre, Davide Della; Donnini, Riccardo; Villa, Elena; Passaretti, Francesca
Abstract: In this work, a pseudoelastic damper composed by NiTi wires is tested at 0.5, 1 and 2 Hz for 1000 mechanical cycles. The damping performances were evaluated by three key parameters: the damping capacity, the dissipated energy per cycle and the maximum force. During testing, the temperature of the pseudoelastic elements was registered as well. Results show that the damper assures a bi-directional motion throughout the 1000 cycles together with the maintenance of the recentering. It was observed a stabilization process in the first 50 mechanical cycles, where the key parameters reach stable values; in particular it was found that the damping capacity and the dissipated energy both decrease with frequency. Besides, the mean temperature of the pseudoleastic elements reaches a stable value during tests and confirms the different response of the pseudoelastic wires accordingly with the specific length and stain. Finally, interesting thermal effects were observed at 1 and 2 Hz: at these frequencies and at high strains, the maximum force increases but the temperature of the NiTi wire decreases being in contraddiction with the Clausius–Clapeyron law.